Effect of High Hydrostatic Pressure Intensity on Structural Modifications in Mealworm (Tenebrio molitor) Proteins - Abir Boukil; Alice Marciniak; Samir Mezdour; Yves Pouliot; Alain Doyen (Foods, 2022)
Processing edible insects into protein extracts may improve consumer acceptability. However, a better understanding of the effects of food processing on the proteins is needed to facilitate their incorporation into food matrices. In this study, soluble proteins from Tenebrio molitor (10% w/v) were pressurized using high hydrostatic pressure (HHP) at 70–600 MPa for 5 min and compared to a non-pressurized control (0.1 MPa). Protein structural modifications were evaluated using turbidity measurement, particle-size distribution, intrinsic fluorescence, surface hydrophobicity, gel electrophoresis coupled with mass spectrometry, and transmission electron microscopy (TEM). The observed decrease in fluorescence intensity, shift in the maximum emission wavelength, and increase in surface hydrophobicity reflected the unfolding of mealworm proteins. The formation of large protein aggregates consisting mainly of hexamerin 2 and ⍺-amylase were confirmed by protein profiles on gel electrophoresis, dynamic light scattering, and TEM analysis. The typical aggregate shape and network observed by TEM after pressurization indicated the potential involvement of myosin and actin in aggregate formation, and these were detected by mass spectrometry. For the first time, the identification of mealworm proteins involved in protein aggregation phenomena under HHP was documented. This work is the first step in understanding the mealworm protein–protein interactions necessary for the development of innovative insect-based ingredients in food formulations.